2016
DOI: 10.2147/ppa.s115090
|View full text |Cite
|
Sign up to set email alerts
|

The state of multiple sclerosis: current insight into the patient/health care provider relationship, treatment challenges, and satisfaction

Abstract: BackgroundManaging multiple sclerosis (MS) treatment presents challenges for both patients and health care professionals. Effective communication between patients with MS and their neurologist is important for improving clinical outcomes and quality of life.MethodsA closed-ended online market research survey was used to assess the current state of MS care from the perspective of both patients with MS (≥18 years of age) and neurologists who treat MS from Europe and the US and to gain insight into perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 19 publications
2
65
0
Order By: Relevance
“…The consequences of patients not engaging with their own healthcare are, not surprisingly, borne most heavily by the patients themselves and their families, and include emotional, physical, social and financial implications (Rieckmann et al, 2015). Patients have better health outcomes when involved in their own healthcare; motivated patients show improved treatment adherence, reduced risk factors and improved health outcomes (Rieckmann et al, 2015;Tintoré et al, 2016). A shared decision-making approach between HCPs and PwMS is essential for patient-centred care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of patients not engaging with their own healthcare are, not surprisingly, borne most heavily by the patients themselves and their families, and include emotional, physical, social and financial implications (Rieckmann et al, 2015). Patients have better health outcomes when involved in their own healthcare; motivated patients show improved treatment adherence, reduced risk factors and improved health outcomes (Rieckmann et al, 2015;Tintoré et al, 2016). A shared decision-making approach between HCPs and PwMS is essential for patient-centred care.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the early views of HIV/AIDS patients and advocates, both PwMS and HCPs believe that collaborative interactions are required to fully understand and address the complex issues involved in MS, and to improve future care; a collective patient-HCP voice is a positive and powerful one. Although a patient-centred approach in MS has started to emerge in the literature (Ballesteros et al, 2017;Col et al, 2017;Colligan et al, 2017) there is still a lack of recognition of the importance of a shared PwMS-HCP perspective in MS care (Tintoré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, less participation than the patient wanted was associated with a higher level of regret regarding treatment decisions. Similar findings have been reported in patients with multiple sclerosis (MS) in terms of their choice of disease-modifying therapy [27]. Negative communication experiences have led to some patients with MS perceiving their neurologists as having little interest in their day-to-day ongoing difficulties and stress [28,29].…”
Section: Discussionmentioning
confidence: 55%
“…Other studies demonstrated differences between physicians' assumptions about what their patients preferred and patient-stated preferences. [16][17][18] That the tool helped patients understand their own treatment goals and preferences and generated an accurate summary that could be shared with clinicians suggests that this simple approach to preference elicitation may prove helpful in promoting SDM in clinical settings, although further testing is needed. The present finding that preserving brain health was more important than either disability concerns or avoiding relapses is consistent with other studies.…”
Section: Evaluation Of Preference Toolmentioning
confidence: 99%